Remineralization of Enamel Subsurface Lesions by Casein Phosphopeptide-stabilized Calcium Phosphate Solutions - Reynolds, E.C. (Journal of dental research, 1997)
Casein phosphopeptides (CPP) stabilize amorphous calcium phosphate (ACP), localize ACP in dental plaque, and are anticariogenic in animal and in situ human caries models. In this in vitro study, CPP-stabilized calcium phosphate solutions were shown to remineralize subsurface lesions in human third-molar enamel. Solutions were used to examine the effect of CPP-calcium phosphate concentration on remineralization. Other solutions were used to examine the effect of increasing pH, which decreased the concentrations of free calcium and phosphate ions and increased the level of CPP-bound ACP. Although most of the remineralizing solutions were supersaturated with respect to the amorphous and crystalline calcium phosphate phases, the solutions were stabilized by the CPP such that spontaneous precipitation of calcium phosphate did not occur. After a ten-day remineralization period, enamel lesions were sectioned, subjected to microradiography, and the mineral content determined by microdensitometry. All solutions deposited mineral into the bodies of the lesions, with the 1.0% CPP-calcium phosphate (pH 7.0) solution replacing 63.9 ±20.1% of mineral lost at an averaged rate of 3.9 ± 0.8 x 10-8 mol hydroxyapatite/m2/s. The remineralizing capacity was greater for the solutions with the higher levels of CPP-stabilized free calcium and phosphate ions. Remineralization was not significantly correlated with either the CPP-bound ACP or the degrees of saturation for hydroxyapatite, octacalcium phosphate, or ACP. However, remineralization was significantly correlated with the degree of saturation for dicalcium phosphate dihydrate (CaHPO4.2H2O), but this was attributed to the significant correlation of remineralization with the activity gradients from the solution into the lesion of some calcium phosphate ions and ion pairs, in particular the neutral ion pair CaHPO4 0. The CPP, by stabilizing calcium phosphate in solution, maintain high-concentration gradients of calcium and phosphate ions and ion pairs into the subsurface lesion and thus effect high rates of enamel remineralization.